A catalyst-free and expeditious general synthesis of N-benzyl-N-arylcyanamides under ultrasound irradiation at room temperature - Nasrollahzadeh, Mahmoud; Sajjadi, Mohaddeseh; Varma, Rajender S (Ultrasonics sonochemistry, 2019)
A hitherto unknown, novel and direct approach to the efficient synthesis of N-benzyl-N-arylcyanamides is described via N-benzylation of a variety of arylcyanamides with benzyl bromide under ultrasound irradiation condition at room temperature; assorted N-benzyl-N-arylcyanamides are expeditiously accessible in excellent yields. The salient features of this approach include a very simple and clean reaction, higher yields obtained under mild conditions in an environmentally benign protocol. Additionally, easy isolation of the desired products without any tedious purification renders the present protocol a suitable alternative to desirable organic disubstituted cyanamides.
Keywords: N-Benzyl-N-arylcyanamides; Benzyl bromide; Cyanamides; Ultrasound irradiation